Parent satisfaction with sustained home visiting care for mothers and children: an integrative review - Kie Kanda; Stacy Blythe; Rebekah Grace; Lynn Kemp (BMC, 2022)
Abstract Aim To synthesise and analyse the existing literature regarding parent satisfaction with sustained home visiting care for mothers and children. Background Sustained home visiting is a service delivery mechanism of both prevention and intervention, in which people receive structured support services within their home environment over an extended period of months or years. For the purposes of this paper, sustained home visiting refers to in-home nursing support to address health inequities for mothers and young children. Sustained home visiting programs have been found to support improved health, wellbeing, and developmental outcomes for children and families. However, there is limited knowledge with regards to the level of parent satisfaction with care provided at home, and the factors and elements of care parents perceive to be critical to their satisfaction. It is important for healthcare practitioners to understand what practices and process parents consider to be a priority in securing their ongoing engagement. Design Integrative review. Data sources PubMed/Medline, CINAHL, Embase, and PsycINFO. Methods A multi-step approach was used to search and retrieve peer-reviewed studies from the databases. Study selection, data extraction, data synthesis and critical appraisal were undertaken by two independent researchers. Results A total of 13 studies met the inclusion criteria, including nine quantitative and four qualitative studies. The review found that parents provided with home visiting interventions had higher levels of satisfaction with care than those who received routine or facility-based care. Service dose was a factor associated with parent satisfaction, however, the direction of impact on parent satisfaction was mixed. Other elements of care parents perceived as important to service satisfaction included the nurse-client relationship, being treated with respect, empowerment, and emotional support. Conclusion While it is critically important that home visiting practitioners provide evidence-based care and interventions, it is equally important that services are delivered in the context of positive and empowering relationships. Further research is recommended to understand the care process and mechanisms that enhance parent satisfaction and positive experiences, providing optimal quality of care.